2010
DOI: 10.1111/j.1552-6909.2010.01105.x
|View full text |Cite
|
Sign up to set email alerts
|

How Nurses Assist Parents Regarding Life Support Decisions for Extremely Premature Infants

Abstract: Objective-To describe nurse behaviors that assisted parents to make life support decisions for an extremely premature infant before and after the infant's birth.Design-Qualitative, longitudinal, collective case study where interviews were done pre-and postnatally and medical chart data were collected.Setting-Interviews were conducted face-to-face in a private room in the hospital, in the mother's home, or over the telephone.Participants-A sample of 40 cases (40 mothers, 14 fathers, 42 physicians, 17 obstetric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
63
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(64 citation statements)
references
References 23 publications
0
63
0
1
Order By: Relevance
“…Parents needed to know the benefits and adverse effects of treatments (Einarsdottir, 2009) with ample time to ask questions (Kavanaugh et al, 2010). Parents sought and/or relied on the HCPs’ knowledge and opinion about which treatment options were best for the child (Bluebond-Langner et al, 2007; Partridge et al, 2005; Rempel et al, 2004; Sharman et al, 2005) and what scientific evidence supported the efficacy of the treatment (Ellinger and Rempel, 2010; Rempel et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Parents needed to know the benefits and adverse effects of treatments (Einarsdottir, 2009) with ample time to ask questions (Kavanaugh et al, 2010). Parents sought and/or relied on the HCPs’ knowledge and opinion about which treatment options were best for the child (Bluebond-Langner et al, 2007; Partridge et al, 2005; Rempel et al, 2004; Sharman et al, 2005) and what scientific evidence supported the efficacy of the treatment (Ellinger and Rempel, 2010; Rempel et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…Initially objective and neutral communication from HCPs left parents feeling that HCPs had little hope of a positive outcome (Payot et al, 2007; Rempel et al, 2004). The lack of hopeful communication led to a strained relationship between the parents and HCPs because parents were still hoping for their child to be cured of the illness, while they thought providers had ‘given up’ (Kavanaugh et al, 2010). Opposite assessments of hope can create mistrust between parents and HCPs, which leaves parents to advocate for their child by protecting against the perceived negative recommendations of HCPs (Kavanaugh et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, parents of infants in the NICU have been asked to identify behaviors of nurses that helped to support their decision making (emotional support, provision of information, and the physical care of the infant and family emerged as important factors) (Kavanaugh, Moro et al 2010). A survey of neonatology fellows found that 40% had had no formal training regarding how to communicate effectively with parents having to make medical decisions (Boss, Hutton et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…As in our study, recent articles of parental experiences cited nurses as the caregivers providing the most emotional support through this process. 12,[30][31][32] This support often comes in the form of memory making and bereavement support. The parents in our study stressed importance of these areas of palliative care.…”
Section: Additional Comments Left By Neonatologistsmentioning
confidence: 99%